One-step synthesis of highly pure and well-crystallized vertically aligned carbon nanotubes. (March 2021) - Charon, Emeline; Pinault, Mathieu; Mayne-L'Hermite, Martine; Reynaud, Cécile
Abstract: The one-step aerosol-assisted catalytic chemical vapor deposition (CCVD) process, when operated in a H2 -based carrier gas, is shown to be effective at an extremely low ferrocene content (0.1 wt% in toluene), which enables to efficiently prepare forests of vertically aligned multiwalled carbon nanotubes (VACNTs) with high purity and good crystalline level. The resulting iron content in VACNT sample is only 0.5 wt% corresponding to a high catalytic yield of 200 while the steady growth rate (20 μm/min) is maintained at a significant value. The iron content in the sample is found proportional to the ferrocene concentration in the precursor, and when it decreases, a noticeable reduction in the iron encapsulation frequency in the nanotube channel is plainly observed. Lowering the ferrocene concentration generates a reduction in the VACNT number density while the growth rate increases and CNT diameters and crystalline structure remain similar. Such significant purity and crystalline levels involves a high oxidation resistance of the VACNT forest. These results, together with the in-situ continuous growth feature of the one-step aerosol assisted CCVD process, open up towards a new VACNT range made of pure and well-crystallized multi-walled carbon nanotubes, which is of interest for industrial production and commercial applications. Graphical abstract: Image 1